2023
DOI: 10.3390/nu15051123
|View full text |Cite
|
Sign up to set email alerts
|

The Inter-Organ Crosstalk Reveals an Inevitable Link between MAFLD and Extrahepatic Diseases

Abstract: Fatty liver is known to be associated with extra-hepatic diseases including atherosclerotic cardiovascular disease and extra-hepatic cancers, which affect the prognosis and quality of life of the patients. The inter-organ crosstalk is mediated by metabolic abnormalities such as insulin resistance and visceral adiposity. Recently, metabolic dysfunction-associated fatty liver disease (MAFLD) was proposed as a new definition for fatty liver. MAFLD is characterized by the inclusion criteria of metabolic abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…A previous cross-sectional analysis by Miao et al studied the relationship between lung function parameters and fibrosis severity in metabolic associated fatty liver disease (MAFLD) patients and found an independent association between MAFLD and impaired pulmonary function, aligning with our findings 31 . Tsutsumi et al also found MAFLD to be an independent factor for COPD, suggesting a link via low-grade inflammation 32 . Another study investigating non-alcoholic fatty liver disease (NAFLD) prevalence and severity in patients with COPD showed a substantial prevalence of steatosis, NASH, and fibrosis, and identified obesity and insulin resistance as key contributing factors 18 .…”
Section: Discussionmentioning
confidence: 96%
“…A previous cross-sectional analysis by Miao et al studied the relationship between lung function parameters and fibrosis severity in metabolic associated fatty liver disease (MAFLD) patients and found an independent association between MAFLD and impaired pulmonary function, aligning with our findings 31 . Tsutsumi et al also found MAFLD to be an independent factor for COPD, suggesting a link via low-grade inflammation 32 . Another study investigating non-alcoholic fatty liver disease (NAFLD) prevalence and severity in patients with COPD showed a substantial prevalence of steatosis, NASH, and fibrosis, and identified obesity and insulin resistance as key contributing factors 18 .…”
Section: Discussionmentioning
confidence: 96%
“…MAFLD is part of a complex, multi-organic set of disorders, rather than merely a liver condition. 27 It is fueled by intricate gene-environment interactions, creating a dysfunctional metabolic medium with a range of outcomes. 28 Based on the proposed criteria, MAFLD is diagnosed when patients with hepatic steatosis meet one or more of the following three criteria: Overweight or obese, T2DM, or signs of metabolic dysregulation (Increased waist circumference, high blood pressure, low HDL cholesterol levels, hypertriglyceridemia, impaired fasting plasma glucose, IR, and chronic subclinical inflammation are at least two of the risk factors.)…”
Section: Introductionmentioning
confidence: 99%
“…Multiorgan crosstalk plays a vital role in the development and advancement of various liver diseases, including NAFLD and alcohol-associated liver disease (ALD) [ 6 , 7 ]. Various organs, including the heart, kidneys, intestines, lungs, and pancreas, interact with the liver through complex signaling pathways and molecular mediators [ 8 ]. This crosstalk is mediated by factors such as hepatokines, myokines, extracellular vesicles, and immune cells, with dysfunctional crosstalk leading to multiorgan diseases and complications [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%